Pengering Maggot berbasis IoT (POTbIoT) untuk Mengatasi Keterbatasan Pakan Ternak - Prasetiya, Eriska Hadi; Maulidina, Miftakhul; Puspitasari, M. Dewi Manikta; Suwardono, Agus (Nusantara of Engineering (NOE), 2024)
Currently, there is an urgency for the need for quality animal feed that can meet the needs of all farmers. One way to overcome this is to design an efficient tool to produce quality animal feed. This study aims to design and build an IoT-based maggot dryer to increase the efficiency of the maggot drying process. Maggots, larvae of the Black Soldier Fly, are a potential alternative source of protein for livestock and fish feed. The tool designed uses a DS18B20 sensor to detect temperature and heat the maggots automatically using a Tubular Heater. This tool can be controlled remotely and provides notification when the drying process is complete by utilizing IoT. The method used is procedural development with testing carried out on several parameters such as temperature and drying time. The results of the study showed that the IoT-based maggot dryer is more efficient than the manual drying method because it can reduce the time and energy required, and produce high-quality dry maggots. This tool is expected to help farmers improve the quality and quantity of maggot production.